2021
DOI: 10.3390/antiox10081217
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin in Tartary Buckwheat Induces Autophagy against Protein Aggregations

Abstract: Tartary buckwheat is used as an ingredient in flour and tea, as well as in traditional Chinese medicine for its antioxidant effects. Here, we found that an ethanol extract of tartary buckwheat (TBE) potently induced autophagy flux in HeLa cells by suppressing mTORC1 activity, as revealed by dephosphorylation of the mTORC1 substrates Ulk1, S6K, and 4EBP, as well as by the nuclear translocation of transcriptional factor EB. In addition to non-selective bulk autophagy, TBE also induced aggrephagy, which is define… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
0
0
Order By: Relevance
“…Recently, chaperonin-containing TCP-1 subunit 2 (CCT2) has been identified as novel receptor for solid protein aggrephagy through a LC3-labeled HTT inclusion bodies purification strategy followed by proteomic determination [44]. Some potent pharmacological aggrephagy inducers have also been revealed and show neuroprotective capabilities in neurodegenerative diseases, such as PD180970 and XCT 790 [45][46][47][48].…”
Section: Aggrephagymentioning
confidence: 99%
“…Recently, chaperonin-containing TCP-1 subunit 2 (CCT2) has been identified as novel receptor for solid protein aggrephagy through a LC3-labeled HTT inclusion bodies purification strategy followed by proteomic determination [44]. Some potent pharmacological aggrephagy inducers have also been revealed and show neuroprotective capabilities in neurodegenerative diseases, such as PD180970 and XCT 790 [45][46][47][48].…”
Section: Aggrephagymentioning
confidence: 99%
“…However, secondary metabolites such as rutin or quercetin are also abundant in buckwheat grains, which have anti-tumor properties, e.g., lung adenocarcenoma [1]. According to Ikari et al [2] quercetin extracted from buckwheat enhances autophagy against protein aggregation by suppressing mTORC1 activity. An experiment conducted by Wang et al, altering the diet of rats, showed that buckwheat consumption led to a higher concentration of short fatty acids (SCFA) and increased levels of Lactobacillus, Blautia, and Akkermansia strains in the gut.…”
Section: Introductionmentioning
confidence: 99%